Harmonic Distortion Analysis Of On-grid Photovoltaic Panel Integration In Load Sharing Scheme - Santoso, Satria Adji; Ulinuha, Agus (ELKHA : Jurnal Teknik Elektro, 2025)
Harmonic analysis is crucial to maintain the system power quality, especially in photovoltaic panels with load sharing scheme. Previous studies have discussed the impact of harmonic distortion on electric power systems in general, but there is still limited discussion on on-grid photovoltaic panel systems without the load-sharing scheme. Harmonic is a distortion phenomenon of current and voltage that is higher than fundamental frequency. The consumption of nonlinear loads contributes to the rising of harmonic distortion that has a bad impact on the system's power quality. This study aims to analyze and compare the levels of harmonic distortion on on-grid photovoltaic panels with a load-sharing scheme and evaluate the suitability with the IEEE 519-2014 standard. The result of this study shows that the Total Harmonic Distortion (THD) on the current   (THDi) in PLN"™s load and network exceeds the limit that is stipulated in IEEE 519-2014. THD current in PLN"™s loads and network is higher than the output current from the on-grid inverter because of the consumption of the nonlinear load. Meanwhile, Total Harmonic Distortion (THD) on the voltage (THDv) in the on-grid inverter, electric network, and load tends to be lower and still within the safe limit. This study is expected to support the implementation of an effective preventive strategy to reduce harmonic distortion on the performance of on-grid photovoltaic panels that will be optimum in the load-sharing scheme.